REVITALISASI KEPEMIMPINAN PENDIDIKAN GLOBAL BERBASIS BUDAYA DI SDN 08 VII KOTO SUNGAI SARIK: STRATEGI TRANSFORMASI BUDAYA ORGANISASI SEKOLAH - Weni Yulastri; Putri Yulia Mandasari; Wendri Gusdi; Mulya Syafrina; Emi Sofia; Seri Sufani; Dutika (STKIP Subang, 2025)
The issues in the implementation of culture-based global educational leadership at SDN 08 VII Koto Sungai Sarik reflect weak teacher discipline, low integration of local cultural values, insufficient motivation to improve competencies, and a weak school organizational culture. This study aims to analyze the causes and impacts of these problems and propose strategic approaches for improvement. The research method uses a qualitative approach based on literature studies and participatory observation. The results indicate that approaches including character habituation, strengthening technology, integrating culture into learning, and consistent self-reflection can drive school culture transformation. Effective leadership begins with leaders setting examples, cultivating noble values, and synergy between local and global values in the learning process.